Peer-to-peer support: digital networking in aphasia to improve quality of life (PeerPAL) - Kurfess, Christina; Corsten, Sabine; Nickel, Maren Tabea; Knieriemen, Marie; Kreiter, Daniel; Lauer, Norina (Frontiers in Communication, 2023)
Background: People with aphasia (PWA) often suffer from reduced participation and quality of life. Nevertheless, there are currently only a few specific interventions that respond to this problem. Participation and quality of life could be increased by interacting with peers who have similar experiences. Digital social networks could stimulate an autonomous interaction. However, digital social networks need to be adapted to the specific needs of PWA. Therefore, a participatory, agile process should be chosen to develop such a solution. The research project consists of a total of three phases. In the third phase-feasibility and preliminary efficacy-that will be described in the article, the impact of the app on PWA will be evaluated. Aims: The overarching aim of our study is to provide preliminary efficacy of the intervention. In addition to digital interaction, personal encounters between PWA should be encouraged. As a result, we expect an improvement in quality of life of PWA. Methods: The evaluation takes place in a pretest-posttest design with a total of 48 PWA. Half of the participants will be assigned to the delayed intervention group and the other half to the immediate intervention group. Questionnaires on quality of life (SAQOL-39, GHQ-12), depression (GDS, DISCs), communicative participation (CPIB), and social support (F-SozU) will be conducted at inclusion (t0), after 3 months of app use (t1), and after another three months for follow-up (t2). In addition to the quantitative measures, interviews will take place. Responses will be analysed using Thematic Analysis. Discussion: The app will be the first social network tool that is systematically developed with PWA. Initial indications from the first phases are that the app can be used by PWA, so that the evaluation of this app version can take place in the third phase. Results of this study can provide an initial indication of whether social network support is a suitable intervention. Findings will help provide information on the feasibility of digital connectivity for PWA. Preliminary findings on its impact on the participation and quality of life of PWA could be made available.